2013
DOI: 10.1371/journal.pone.0064875
|View full text |Cite
|
Sign up to set email alerts
|

The Cell Wall-Targeting Antibiotic Stimulon of Enterococcus faecalis

Abstract: Enterococcus faecalis is an opportunistic nosocomial pathogen that is highly resistant to a variety of environmental insults, including an intrinsic tolerance to antimicrobials that target the cell wall (CW). With the goal of determining the CW-stress stimulon of E. faecalis, the global transcriptional profile of E. faecalis OG1RF exposed to ampicillin, bacitracin, cephalotin or vancomycin was obtained via microarrays. Exposure to the β-lactams ampicillin and cephalotin resulted in the fewest transcriptional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 57 publications
3
30
0
1
Order By: Relevance
“…As mentioned above, operons for two such transporters were previously identified in the genome of E. faecalis by a comparative genomics study, namely, EF2050-2049 and EF2752-2751 (16). Although our proteomic study identified only the former transporter, both loci were found to be upregulated in response to bacitracin by transcriptome analysis (8). We therefore decided to investigate these two transporters in more detail, regarding both their role in bacitracin resistance and their regulation.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…As mentioned above, operons for two such transporters were previously identified in the genome of E. faecalis by a comparative genomics study, namely, EF2050-2049 and EF2752-2751 (16). Although our proteomic study identified only the former transporter, both loci were found to be upregulated in response to bacitracin by transcriptome analysis (8). We therefore decided to investigate these two transporters in more detail, regarding both their role in bacitracin resistance and their regulation.…”
Section: Resultsmentioning
confidence: 88%
“…In accordance with the need for a better understanding of the response of E. faecalis to antibiotics that inhibit cell wall synthesis, a recent transcriptomic study identified a large number of genes that were upregulated after exposure to ampicillin, cephalothin, vancomycin, and bacitracin (8). Of these compounds, bacitracin elicited the broadest response, affecting genes with functions in cell wall maintenance, metabolism, and transport processes.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The VanH dehydrogenase converts pyruvate into Other highly upregulated genes have previously been implicated in the enterococcal extracytoplasmic stress response (Table 2; see also Data Set S1). We identified overlap between the H-CHG transcriptomic response in E. faecium 1,231,410 with the transcriptomic response of E. faecalis OG1RF to the cell wall-active antibiotics ampicillin, bacitracin, cephalothin, and vancomycin (38) and with the E. faecalis OG1X response to the plasmid-encoded Fst toxin, which likely interacts with the OG1X cell membrane, causing stress (39,40). Further, mutations in four genes in our data set are associated with daptomycin nonsusceptibility in E. faecalis and E. faecium (41)(42)(43)(44).…”
Section: Resultsmentioning
confidence: 96%
“…B. cereus is normally associated with food poisoning that is characterized by either diarrhoea and abdominal distress or nausea and vomiting (Senesi and Ghelardi, 2010). It is also an opportunistic pathogen in immunocompromised patients causing severe endophthalmitis, bacteremia, septicemia, endocarditis, pneumonia, meningitis, gastritis, and cutaneous infections (Senesi and Ghelardi, 2010); Vibrio bacteria is incriminated in mostly gastrointestinal and extra-intestinal diseases in man (Health protection agency, 2007); Enterococcus bacteria are common causes of nosocomial infections (Arias et al, 2010), such as catheter-associated urinary tract infections, endocarditis as well as surgical and burn wound infections (Abranches et al, 2013) ; E. coli bacteria, mostly the shiga toxin producing serotypes cause mild to bloody diarrhoea, haemorrhagic colitis, and hemolytic-uremic syndrome (HUS) (Brooks et al, 2005). Treatment of these various bacterial infections is, however, being hindered by the prevalence of antibiotic resistant strains (Furtula et …”
Section: Introductionmentioning
confidence: 99%